Quality assessment and feeding impact of Moringa feed on intake, digestibility, enteric CH4 emission, rumen fermentation, and milk yield - Bashar, Muhammad Khairul; Huque, Khan Shahidul; Sarker, Nathu Ram; Sultana, Nasrin (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: This experiment was designed to assess the quality and to evaluate the feeding impact of moringa feed on intake, digestibility, rumen fermentation, methane (CH4) production, and milk yield. Materials and methods: According to body weight and exit–entry average daily milk production, fifteen BLRI cattle breed-1 lactating cows of 3rd or 4th stage of parturition with wk 3 and 4 of calving were selected and were equally and randomly distributed into three dietary groups. One group of cows was fed a control diet (T0) consisting of 1:1 dry matter (DM) of Napier silage and conventionally mixed concentrate. The other two groups were fed a control diet by randomly replacing i) 50% (T1) or ii) 100% (T2) of its concentrate with moringa feed. The three dietary groups were balanced nutritionally based on energy and protein following the Bangladesh Standards and Testing Institution (BSTI) standard. Results: The concentrate mixture was replaced with moringa feed to increase the feed efficiency and to reduce the DM or crude protein intake (p < 0.05) per 100 kg of metabolic body weight. The T2 group flourished with the highest (p < 0.05) amount of raw milk and also 4% fat-corrected milk (4.39 and 4.59 kg/day, respectively) compared to the T0 group (3.30 and 3.49 kg/day, respectively). However, it increased (p < 0.05) the concentration of total volatile fatty acid and decreased (p < 0.05) the blood and milk cholesterol, and ammonia-nitrogen (NH3-N) was reputed by adding moringa feed into the T0 group, without showing any significant (p > 0.05) change in CH4 production, fat, solid not fat, lactose or protein content of milk. Conclusion: Therefore, moringa feed increased the productivity in dairy cows, replacing the whole concentrate diet. J. Adv. Vet. Anim. Res., 7(3): 521-529, Sep 2020 http://doi.org/10.5455/javar.2020.g449